Санітарно-гігієнічна оцінка молока корів за субклінічного маститу в умовах лабораторії ветеринарно-санітарної експертизи на ринку «Самвел» міста Комсомольськ Полтавської області - Корейба, Людмила Володимирівна; Koreyba, Ludmila; Ларченко, Ольга Іванівна; Larchenko, Olga; Терешок, Вадим Вадимович; Tereshok, Vadim (Інститут ветеринарної медицини НААН, 2015)
Встановлено, що субклінічний мастит у корів проявляється зниженням санітарно-гігієнічної якості молока та показників його безпеки за рахунок зростання у ньому вмісту соматичних клітин і бактеріального обсіменіння; підвищення кислотності та зниження щільності, присутності сапрофітів, умовно-патогенної і патогенної мікрофлори. Production of quality and safe dairy products impossible without high- quality and safe raw milk. Its nutritional value is predetermined by protein, fat, carbohydrates, minerals, vitamins, etc. Sanitary-hygienic quality of milk is characterized by such factors as: protein, fat, density, acidity, the number of somatic cells, the presence of impurities of mastitis milk, foreign bodies and general bacterial contamination. Violation of sanitary norms and rules in milk production and mastitis in cows leads not only to reduce the nutritional value but also to increase its danger to human health, especially children. Milk obtained from cows with subclinical mastitis differs significantly from the normal milk by chemical composition, physico-chemical and biological features. Sanitary quality of collective milk, especially his overall bacterial contamination, much depends on mastitis situation in the dairy sector. In cases when the farm has up to 10% of cows with subclinical mastitis sanitary quality of milk deteriorating twice. Due to the intensive development of dairy farming, the creation of large farms and complexes of various types of milk production and the introduction of modern milking units occur a problem to combat mastitis and improve sanitary and hygienic quality of milk. Every year in terms of farms and agricultural enterprises subclinical form of mastitis is diagnosed in 22–29% of cows. Timely detection of inflammation in the mammary gland of the cows in the absence of severe clinical signs and sanitary and hygienic changes in milk is problematic task for specialists of veterinary medicine. Therefore, the issue of technology to obtain the milk of high sanitary quality in a production environment is important and needs further study.
Sanitary and hygienic evaluation of the milk from cows with subclinical mastitis in a laboratory of veterinary and sanitary expertise in the “Samvel” market of Komsomolsk town Poltava region
Keywords: корови; cows; мастит; mastitis; молоко; milk; патогенна мікрофлора; pathogenic microflora; бактеріальне обсіменіння; bacterial contamination; жирність; fat content; кислотність; acidity; щільність; density; соматичні клітини; somatic cells